Мультиполевая модель импульсного электромеханического преобразователя - Болюх, Владимир Федорович; Назаренко, Сергей Александрович; Рассоха, Максим Алексеевич (НТУ "ХПИ", 2009)
Problem-solving questions emerging during the development of mathematical models of complex construction, in the availability of action electromagnetic fields of the different nature, are considered in article. For pulsed inductive electromechanical converter is offered multi-fields model, which is based on decision interconnected unsteady field problems of the electromagnetism, mechanic and thermal conductivity, taking into consideration for nonlinear parameters with use the method by final element and iterative algorithms. They experimental studies are organized, well concordant with features and parameters of the electromechanical converter.
Keywords: энергосбережение; механическое поле; электромагнитное поле; тепловое поле; термопрочностное поле; электромеханический преобразователь; математическая модель; электромеханика; мультиполевая модель; импульсный преобразователь